Please wait...
1800-212-7858 (Toll Free)
9:00am - 8:00pm IST all days

or

Thanks, You will receive a call shortly.
Customer Support

You are very important to us

For any content/service related issues please contact on this toll free number

022-62211530

Mon to Sat - 11 AM to 8 PM

If the p th term of an AP is a and q th term is b then show that the sum of its first (p+q) terms is p+q/2[a+b+a-b/p+q][2p+1].

Asked by Sneha George 10th February 2011, 10:20 AM
Answered by Expert
Answer:
Dear student,
 

Let 'α' be the first term, and 'd' the common difference of the A.P..

Then,

T(n) = α + (n-1)d

S(n) = (n/2) [ 2α + (n-1) d ] ................. (1)


Now, given that : T(p) = a and T(q) = b.

∴ α + (p-1)d = a .......... (2)

α + (q-1)d = b .......... (3)

Subtracting (3) from (2),

 (p-q)d = (a-b)

∴ d = (a-b) / (p-q) ....................... (4)

Adding (2) and (3),

2α + (p+q-2)d = a + b

∴ [ 2α + (p+q-1)d ] - d = a + b

∴ [ 2α + (p+q-1)d ] = (a+b) + d

∴ from (4),

[ 2α + (p+q-1)d ] = (a+b) + (a-b)/(p-q) .......... (5)

Putting n = (p+q) in(1), and then using (5),

S(p+q) = [ (p+q)/2 ]· [ 2α + (p+q-1)d ]

           = [ (p+q)/2 ]· [ (a+b) + (a-b)/(p-q) ]

We hope that clarifies your query.

Regards,

Team

TopperLearning

Answered by Expert 10th February 2011, 11:43 AM
Rate this answer
  • 1
  • 2
  • 3
  • 4
  • 5
  • 6
  • 7
  • 8
  • 9
  • 10

You have rated this answer /10

Your answer has been posted successfully!

Chat with us on WhatsApp